UKURAN PERTAMA KALI MATANG GONAD DAN SELEKTIVITAS JARING INSANG IKAN NILA (OREOCHROMIS NILOTICUS) DI WADUK JATILUHUR, JAWA BARAT - Warsa, Andri; Astuti, Lismining Pujiyani (Research Center for Biology-Indonesian Institute of Sciences, 2019)
A gillnet is a common fishing gear for exploitation and fish capture at Jatiluhur Reservoir. The fish size captured by the gillnet depends on the mesh size for its selective fishing gear. Determination of gillnet mesh size is one of effort for fisheries management. The management of nile tilapia (Oreochromis niloticus) is based on gillnet selectivity and reproductive biology of nile tilapia. The aim of the research was to estimate length at the first mature (Lm) and gillnet selectivity for nile tilapia. The research was conducted at February-September 2017 through experimental fishing using gillnet with 1.0?4.0 mesh size (interval 0.5 inch). The gillnet installation was performed at six stations, namely Cihuni-Cibadak, Sungai Cikanyayan, Sungai Ciririp, Sungai Cihonje, Pasir Kole and Cilalawi. The Lm of nile tilapia was 18.3 and 23.3 cm for female and male, respectively. The total length retained in the gillnet with the highest probability for mesh size 1.0; 1.5; 2.0; 2.5; 3.0; 3.5 and 4.0 inches were 9.5; 12.5; 14.5; 18.5; 20.5; 26.5 and 30.5 cm, respectively. The minimum mesh size used for nile tilapia exploitation was ?3 inches because it was able to catch nile tilapia with the total length larger than Lm (Lc>Lm) and with an SPR value of > 40% so that the tilapia resource in the Jatiluhur Reservoir remains sustainable.